FEDORA 14 DENGAN VIRTUAL SEBAGAI PEMBELAJARAN LINUX FUNDAMENTAL UNTUK MAHASISWA AMIK BSI TANGERANG - Hardiyan Hardiyan (LPPM Universitas Bina Sarana Informatika, 2011)
Fedora is a Linux-based operating system that is always free for anyone to use, modify and distribute it. Linux users in Indonesia is very less, one of which can be viewed from a computer learning at campus. So far learned linux on Campus AMIK BSI Tangerang obtained 5th Semester. With so to be able to learn it should be on their own or training outside campus. On one hand it is difficult for users to install the Linux operating system, due to limited knowledge. Therefore, in this study described the use of Fedora Linux version 14 in a virtual form to be learned. By using VirtualBox to be one alternative for basic Linux users to more easily learn the Linux operating system, because it can run on windows operating system without destroying the existing system. Keywords: Fedora 14, Operating System, Virtual